Potato Processing Industry By-products and Their Evaluation in Animal Nutrition - Pınar Özdemir; Hatice Basmacıoğlu Malayoğlu (Turkish Journal of Agriculture: Food Science and Technology)
All around the world, particularly in developed countries, fresh potato consumption decreased while the consumption as fast food, snack and convenience food was increased. Potato processing industry has by-products such as cull potato, peel, pulp, and waste water. These by-products can be utilized for production of ethyl alcohol, single cell protein, microbial enzymes, lactic acid, organic fertilizer and bioethanol. The pulp obtained from the processing of potato for starch production can be considered as an energy source with starch content in animal nutrition. Recently, potato peel with the contents of bioactive compounds (chlorogenic, caffeic, gallic, protocatechuic acids) and their antioxidant and antimicrobial effects have been intensely focused on. Conversion of by-products of potato processing industry into value-added products is economically important. It was reviewed here by-products of potato processing industry and their evaluation in animal nutrition.